Implementasi Sistem Coretax dalam Pelaporan SPT Masa PPN pada PT ABC - Oktarina, Widiasari; Oryza Tannar (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
Technological developments are driving the transformation of tax administration systems, one of which is through the implementation of CoreTax for reporting Periodic VAT Tax Returns. This study aims to implement this system at PT ABC using a qualitative descriptive approach. Data were obtained through interviews, direct observation, and documentation from various taxpayers and employees involved in tax reporting. The results indicate that the use of CoreTax can accelerate the reporting process and reduce errors thanks to the automated system and integration with e-Billing and e-Invoice services. However, challenges remain, such as limited internet infrastructure, lack of user education, and technical difficulties accessing the system. Differences in digital literacy levels also affect user trust in the application. Therefore, improving infrastructure quality, intensive training, and system improvements are urgently needed to optimize CoreTax’s use in supporting tax modernization.